Causes of hunger - Cohen, Marc J.; Reeves, Don (International Food Policy Research Institute, 1995)
The persistence of hunger in a world of plenty is the most profound moral contradiction of our age. Nearly 800 million people in the developing world (20 percent of the total population) are chronically undernourished. At least 2 billion suffer from vitamin and mineral deficiencies. Yet since the mid-1970s the world has produced enough food to provide everyone with a minimally adequate diet. Hunger is one piece of a complex of interrelated social ills. It is linked intricately to global economic, political, and social power structures; modes of development and consumption; population dynamics; and social biases based on race, ethnicity, gender, and age. The world community has both the knowledge and the resources to eliminate hunger. Putting these tools to work requires us to ground our choices--small and large, individual and collective, political and economic -- in ethical values, including empowerment and justice, stewardship of common resources for the common good, and affirmation of diversity.